Повторение судьбы: роман / Януш Леон Вишневский - Вишневский Януш Леон (Азбука, 2011)
Экземпляры: ф. 1 (20150313) / Инвентарный номер: 102317 / Цена: 313.00 / Авт.знак: В 55 / ГРНТИ: 17.82 / ББК: 84(4Пол)